Long-acting insulin analogues versus NPH insulin in type 2 diabetes mellitus - Rodríguez-Lay, Elba Giovanna (2019)
nsulin continues to be fundamental for the treatment of diabetes mellitus type 1 and the most appropriate way to treat type 2 diabetes when oral agents do not achieve the goals or if complications occur. Scientific research explores new ways of presenting the drug trying to achieve better effects on metabolic control. Since the 1940s, the presentation of the neutral protamine insulin from Hagedorn NPH has been used relatively successfully. In the 90s, the long-acting insulin analogues glargine and detemir with apparently better possibilities in their action are presented. In the present work, systematic reviews and primary works comparing both insulins are described. It is concluded that no significant differences were found between the use of insulin NPH and insulin analogues glargine and detemir. NPH insulin remains, despite the time, a safe presentation in patients with low risk of hypoglycemia and at a lower cost which explains the preference for its acquisition in health systems, as in our country among others, as well as in social aid organizations as evaluated by the pilot study "CINCI study"